A Qualitative Study Exploring Moral Distress Among Pediatric Resuscitation Team Clinicians: Challenges to Professional Integrity*. Issue 7 (July 2016) - Thomas, Tessy A.; Thammasitboon, Satid; Balmer, Dorene F.; Roy, Kevin; McCullough, Laurence B.
Abstract : Objective: Our study objectives were to explore moral distress among pediatric team clinicians within the context of resuscitation experiences, and determine whether there were any distinctively ethical perspectives on moral distress that could be conceptualized as challenges to professional integrity, rather than to previously described psychological responses of clinicians. Design: Descriptive, exploratory qualitative study. Setting: A large tertiary pediatric academic hospital in Houston, TX. Subjects: Twenty-five PICU resuscitation team clinicians were interviewed from December 2012 to April 2013. Interventions: None. Measurements and Main Results: All clinicians reported experiencing moral distress during certain resuscitations. Twenty-one of 25 clinicians reflected and acknowledged that their sense of professional integrity had been challenged during those resuscitation events. Four main components of resuscitation experience that induced moral distress were identified: 1) experiences where there was lack of understanding of the big picture; 2) experiences where there was suboptimal team leadership; 3) experiences where there was variable meanings to the word "resuscitation"; and 4) experiences were there was uncertainty of role responsibility. Conclusions: The perception of moral distress exists among pediatric clinicians during resuscitations and could be conceptualized as challenges to professional integrity. This ethical framework offers an alternative approach to understanding and investigating the complex layers of moral distress.